The Hippy Love and Humanita Ideology: Giving or Needing? - Penner, Wes; Truax, Charles B. (Canadian Journal of Counselling and Psychotherapy, 2012)
The central question researched was whether transients — hippies -— communicate in a way that is negative and harmful, or whether, consistent with their rhetoric, they project warmth, love, and understanding in their interpersonal relationships. Also, whether compared with trained counselors and teachers, hippies and transients would exhibit, to a person with personal problems, less, as much, or more of the classic "helping" dimensions of genuineness, non-possessive warmth, and accurate empathy. Findings suggest that the more the "helper" approximates the transient hippie reality (as measured by the Omnibus Personality Inventory), the lower his actual communicated levels of the "helping" dimensions.